Development of JAERI Monte Carlo machine and its effective performance - Higuchi, Kenji; Asai, Kiroshi; Akimoto, Masayuki; Kambayashi, Shaw; Tokuda, Shinji; Hasegawa, Yukihiro; Asami, Akira; Sasaki, Makoto (Computer Assisted Methods in Engineering and Science, 2023)
The JAERI Monte Carlo Machine has been developed mainly to enhance the computational performance of numerical simulations with particle models such as Monte Carlo methods. The features of the JAERI Monte Carlo machine are i) vector processing capability for arithmetic operations, ii) special pipelines for fast vector processing in categorizations of particles, iii) enhanced load/store pipelines for indirectly addressed vector elements, iv) parallel processing capability for spatially and phenomenologically independent particles. This paper describes the design philosophy and architecture of the JAERI Monte Carlo machine and its effective performance through practical applications of the multi-group criticality safety code KENO-IV, the continuous-energy neutron/photon transport code MCNP and other codes for particle simulation.